Perawatan Vagina, Kesehatan Lingkungan Dan Pendapatan Keluarga Dengan Kejadian Keputihan Pada Remaja Putri - Risa Pitriani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Problems whitish or so-called flour albus is a problem that has long been an issue for women. Care and maintain a healthy vaginal environment in adolescent girls is important to avoid the occurrence of vaginal discharge. Family income factors also play a role in determining a person’s health status. In 2012 SMP 20 Pekanbaru has the 2nd highest female students in Pekanbaru city, and according to the information part of student teachers and vice-principals, that the SMP Negeri 20 Pekanbaru never get information or counseling from medical personnel about whiteness.Objective: This study aimed to determine the relationship of vaginal care, environmental health and family income with whitish incidence in young women in SMP 20 Pekanbaru in 2013.Methods: This cross-sectional study conducted in April - May 2013 in SMP 20 Pekanbaru. Sampling techniques using techniques total population of 184 people. Measuring instrument used was a questionnaire. Analysis of data using univariate and bivariate analysis with chi-square test.Results: The study showed for the factors Vagina OR = 2.608 (95% CI: 1.427 to 5.767), Environmental Health factor OR = 6.577 (95% CI: 3.256 to 12.112) and Family Income factor OR = 3.343 (95% CI: 1,233- 4.328).Conclusion: There is a relationship vaginal care, environmental health and family income with whitish incidence in young women.Keywords: Whitish, Young, Vagina, Environmental Health, Family income